Mono-, Di- and Tributyltin Derivatives of 1-Hydroxy-2-Naphthoic and 3-Hydroxy-2-Naphthoic Acids. - MANRAL (NEE BORA), DIPTI; SHAH, RANJANA; CHANDRA , MADHUP (Asian Journal of Chemistry, 2010)
Several organotin derivatives of 1-hydroxy-2-naphthoic and 3-hydroxy-2-napththoic acids have been prepared by the interaction of monobutyltin triisopropoxide, dibutyltin diisopropoxide or tributyltin isopropoxide with the latter in various stoichiometric ratios viz. 1 : 1, 1 : 2, 1 : 3 and 2 : 1 in benzene/toluene medium. The compounds thus prepared were obtained generally as coloured solids, excepting the tributyltin derivatives which isolated as dark viscous liquids. However, amongst them those containing isopropoxy group(s) were found to be hygroscopic in nature. All these compounds were characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.